ENHANCING THE WELLBEING OF DIVORCED PERSONS THROUGH SOCIAL WORK SERVICES: SERVICE-USERS’ EXPERIENCES AND SUGGESTIONS - Paul Rembuluwani Mbedzi (Stellenbosch University, 2021)
Divorce is one of the most stressful life events a person can face and it often has adverse consequences. Social work services are of critical importance in enhancing the wellbeing of divorced persons and improving their relationships with their significant others. A qualitative research study was conducted to develop an in-depth understanding of the nature of social work services to divorced persons and the divorced persons’ suggestions regarding social work services. This paper reports the findings, conclusions and recommendations based on interviews conducted with divorced South African men and women from different ethnic groups with the purpose of enhancing the wellbeing of divorced persons through social work services.